2012
DOI: 10.1016/j.jmb.2012.02.044
|View full text |Cite
|
Sign up to set email alerts
|

CC2D1A Is a Regulator of ESCRT-III CHMP4B

Abstract: Endosomal sorting complexes required for transport (ESCRT) regulate diverse processes ranging from receptor sorting at endosomes to distinct steps in cell division and budding of some enveloped viruses. Common to all processes is the membrane recruitment of ESCRT-III that leads to membrane fission. Here, we show that CC2D1A is a novel regulator of ESCRT-III CHMP4B function. We demonstrate that CHMP4B interacts directly with CC2D1A and CC2D1B with nanomolar affinity by forming a 1:1 complex. Deletion mapping re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 75 publications
9
69
0
Order By: Relevance
“…A similar interaction has been reported between the mammalian orthologues of Lgd interact and the orthologues of Shrub, CHMP4a, b, c (Martinelli et al, 2012;Usami et al, 2012). Moreover, in vitro experiments suggest that Lgd1 and Lgd2 can influence the polymerisation of CHMP proteins (Martinelli et al, 2012). We therefore favour the possibility that upon loss of lgd function, Notch is inefficiently incorporated into the ILVs due to a reduction, but not abolishment in the activity of shrub.…”
Section: Prerequisites Of Notch Activation In Lgd Cellssupporting
confidence: 81%
See 1 more Smart Citation
“…A similar interaction has been reported between the mammalian orthologues of Lgd interact and the orthologues of Shrub, CHMP4a, b, c (Martinelli et al, 2012;Usami et al, 2012). Moreover, in vitro experiments suggest that Lgd1 and Lgd2 can influence the polymerisation of CHMP proteins (Martinelli et al, 2012). We therefore favour the possibility that upon loss of lgd function, Notch is inefficiently incorporated into the ILVs due to a reduction, but not abolishment in the activity of shrub.…”
Section: Prerequisites Of Notch Activation In Lgd Cellssupporting
confidence: 81%
“…We have recently shown that Lgd physically interacts with Shrub and is required for its full function (figure 9A, Troost et al, 2012). A similar interaction has been reported between the mammalian orthologues of Lgd interact and the orthologues of Shrub, CHMP4a, b, c (Martinelli et al, 2012;Usami et al, 2012). Moreover, in vitro experiments suggest that Lgd1 and Lgd2 can influence the polymerisation of CHMP proteins (Martinelli et al, 2012).…”
Section: Prerequisites Of Notch Activation In Lgd Cellssupporting
confidence: 65%
“…S1), suggesting a link between the role of TAPE in endosomal trafficking and RLR signaling. Interestingly, recent studies indicated that TAPE/CC2D1A binds to and negatively regulates CHMP4B, a component of the endosomal sorting complexes required for transport (ESCRT) pathway, leading to the inhibition of HIV-1 budding (21,22). These findings further support the importance of TAPE in regulating the endolysosomal compartments.…”
Section: Tape-deficient Mefs and Macrophages Are Impaired In Type I Imentioning
confidence: 62%
“…Numerous electron micrographs exist for ESCRT-III assemblies, but these cannot reveal details like protein -protein interfaces. Currently, crystal structures exist for portions of VPS24/CHMP3, SNF7/CHMP4, and IST1 (Muziol et al 2006;Bajorek et al 2009;Martinelli et al 2012). However, there are no structures of either full-length ESCRT-III subunits, or ESCRT-III hetero-oligomers.…”
Section: Concluding Remarks: Remaining Questions and Future Studiesmentioning
confidence: 99%